Analysis of interior permanent magnet motors with non-overlapping windings - Germishuizen, Johannes Jacobus (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.